Comparative study of empirical analysis and numerical simulation for far-field propagation of tsunamis caused by landslides - Wang Jibao; Deng Hao; Tan Lizi (ITM Web of Conferences)
Landslide tsunamis can have a significant impact on the areas where they are generated and propagate. The far-field propagation of landslide tsunamis in river-type reservoirs is generally calculated using empirical formulas. By utilizing a landslide body in the Three Gorges Reservoir of the Yangtze River, a three-dimensional landslide tsunami numerical model was established based on the FLOW-3D computational fluid dynamics software. The model simulates and analyzes the propagation patterns of landslide tsunamis in real rivers and compares them with commonly used empirical analyses of landslide tsunamis. It also discusses the issues with empirical formulas in practical engineering applications and offers some suggestions.